Comparative Analysis of Legal Protection and Criteria of Well-Known Marks (Indonesia, United States, India, China, and Germany) - I Gede Mahatma Yogiswara Winatha; A.A.Gede Agung Indra Prathama; Putu Chandra Kinandana Kayuan (Universitas Muhammadiyah Malang, 2023)
Trademark functions as a distinguishing mark between goods and/or services of its kind, as well as an identification mark for goods and/or services from the producer concerned. In order to be a well-known and widely recognized mark by the world community, and also to gain a good reputation it requires a very high investment to maintain quality and perform massive promotions in many countries. Considering this, lawful protection of well-known marks is a must. This research uses a normative juridical method by examining regulations and analyzing the previous studies, as well as other relevant legal materials to determine the criteria of well-known marks and the law protection provided for well-known marks in Indonesia. The results of this study indicate that the regulation of the criteria for well-known marks in Indonesia still does not set concretely the minimum number that must be met for each criterion. Furthermore, in principle, Indonesia provides legal protection for well-known marks, both registered and unregistered in Indonesia.